Dielectric properties and ac conductivities of Bi1−xSmxFeO3 ceramics. Issue 196 (12th February 2019) - Sadykov, S. A.; Kallaev, S. N.; Alikhanov, N. M.-R.; Bormanis, K.; Kalvane, A.
Abstract: Dielectric permittivity, dielectric losses and ac-conductivity of polycrystalline Bi1− x Sm x FeO3 ( x  = 0; 0.05; 0.1; 0.15; 0.2) are measured in the frequency range 1 kHz–10 MHz and in the temperature range 25–600 °C. Anomalies have been observed at the 200 °C, 300 °C and at the Néel temperature. It has been demonstrated that doping with Sm has enhanced the dielectric properties and increased conduction in the frequency region <1 MHz. At high frequency (>1 MHz) and at a certain temperature T m, depending on the composition Bi1− x Sm x FeO3, the conductivity reaches a maximum. The results are discussed with reference to the model of correlated barrier hopping.